The Crystal and Molecular Structure of 2-[(3,4-dimethoxybenzylidene)amino]adamantane - Çoruh, U.; Çalış, Ü.; Işík, Ş.; Fun, H.-K. (Wiley-VCH Verlag GmbH, 2002)
The crystal structure of the title compound, C19H25NO2 was determined by single crystal X-ray diffraction technique. The crystal data are Orthorombic, space group Pbca, with a = 9.2119(4), b = 9.5555(4), c = 37.6049(5) Å, Z = 8, T = 293(2) K, MoKα radiation, λ = 0.71073 Å, Mr = 299.40, R = 0.0839 for 1945 reflections with I>2σ(I). The title compound shows intermolecular C-H...O type interactions.
Keywords: 2-[Arylydeneamino]Adamantane Derivatives; Adamantane Derivatives; Antimicrobial Activity